Primary Hyperparathyroidism Presenting as Recurrent Pancreatitis Due to Parathyroid Adenoma - Kumar, Vigneshraja; Nethikoppula, Anil Kumar; Pallavi, N.; Anusha, Nukala; Somalwar, Shrinivas B.; Vaddiraju, Shanthi Sree (Journal of Gastrointestinal and Abdominal Radiology, 2020)
Recurrent attacks of acute pancreatitis as initial manifestation of primary hyperparathyroidism is rare. We report two cases of young women presenting with recurrent attacks of pancreatitis due to parathyroid adenoma. After surgical excision of the parathyroid adenoma, symptoms of pancreatitis resolved, and serum parathormone and calcium levels returned to normal.
Keywords: hyperparathyroidism; recurrent pancreatitis; parathyroid adenoma